A Double-Blind, Adjuvant-Controlled Trial of Human Immunodeficiency Virus Type 1 (HIV-1) Immunogen (Remune) Monotherapy in Asymptomatic, HIV-1-Infected Thai Subjects with CD4-Cell Counts of >300 - Churdboonchart, V. (American Society for Microbiology, 2000)
We examined the effect of a human immunodeficiency virus (HIV)-specific immune-based therapy in Thailand, where access to antiviral drug therapy is limited. A 40-week trial was conducted with 297 asymptomatic, HIV-infected Thai subjects with CD4-cell counts greater than 300 μl/mm(3). Subjects were randomized to receive either HIV type 1 (HIV-1) immunogen (Remune; inactivated HIV-1 from which gp120 is depleted in incomplete Freund's adjuvant or adjuvant control at 0, 12, 24, and 36 weeks at five different clinical sites in Thailand. Neither group received antiviral drug therapy. The a priori primary endpoint for the trial was changes in CD4-cell counts with secondary parameters of percent changes in CD8-cell counts (percent CD4, CD8, and CD4/CD8) and body weight. Subsets of subjects were also examined for changes in plasma HIV-1 RNA levels, Western blot immunoreactivity, and HIV-1 delayed-type hypersensitivity (DTH) skin test reactivity. There was a significant difference in changes in CD4-cell counts that favored the HIV-1 immunogen-treated group compared to those for the adjuvant-treated control group (P < 0.05). On average, for HIV-1 immunogen-treated subjects CD4-cell counts increased by 84 cells by week 40, whereas the increase for the control group was 38 cells by week 40. This increase in CD4-cell count was associated with increased HIV-specific immunogenicity, as shown by Western blotting and enhanced HIV-1 DTH skin reactivity. No significant differences in adverse events were observed between the groups. The results of this trial suggest that HIV-1 immunogen is safe and significantly increases CD4-cell counts and HIV-specific immunity compared to those achieved with the adjuvant control in asymptomatic HIV-1-infected subjects not taking antiviral drugs.